2000
DOI: 10.1210/jcem.85.12.7168
|View full text |Cite
|
Sign up to set email alerts
|

The Endocrine Activities of 8-Prenylnaringenin and Related Hop (Humulus lupulusL.) Flavonoids

Abstract: The female flowers of the hop plant have long been used as a preservative and a flavoring agent in beer, but they are now being included in some herbal preparations for women for "breast enhancement." This study investigated the relative estrogenic, androgenic and progestogenic activities of the known phytoestrogen, 8-prenylnaringenin, and structurally related hop flavonoids. 6-Prenylnaringenin, 6,8-diprenylnaringenin and 8-geranylnaringenin exhibited some estrogenicity, but their potency was less than 1% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(55 citation statements)
references
References 0 publications
1
53
0
Order By: Relevance
“…± 8-Prenylnaringenin and 6-prenylnaringenin, two phytoestrogens from hops [16] [17], are side products formed through the spontaneous cyclization of demethylxanthohumol (4) [18], which is the precursor of potent phytoestrogens and a key intermediate in the synthesis of possible new derivatives of 8-prenylnaringenin. 8-Prenylnaringenin and other prenylated flavonoids showed strong estrogenic activity, whereas no estrogenicity was found in xanthohumol and demethylxanthohumol (4) [19] [20].…”
mentioning
confidence: 99%
“…± 8-Prenylnaringenin and 6-prenylnaringenin, two phytoestrogens from hops [16] [17], are side products formed through the spontaneous cyclization of demethylxanthohumol (4) [18], which is the precursor of potent phytoestrogens and a key intermediate in the synthesis of possible new derivatives of 8-prenylnaringenin. 8-Prenylnaringenin and other prenylated flavonoids showed strong estrogenic activity, whereas no estrogenicity was found in xanthohumol and demethylxanthohumol (4) [19] [20].…”
mentioning
confidence: 99%
“…1-5, and 6-prenylnaringenin Fig. 1-6, are much less active 9 . The total content of prenylflavonoids in beer may add up to 1 mg/L.…”
Section: -2863(9'8-32mentioning
confidence: 92%
“…The total content of prenylflavonoids in beer may add up to 1 mg/L. Additionally, instead of prenyl groups, geranyl (two prenyl units) chains may be introduced, but, as the estrogenicity of geranylated flavonoids is much weaker than that of prenylated flavonoids, these compounds are of minor importance 9 . Prenyl and geranyl groups are biosynthetically added in an activated form (e.g., as pyrophosphates) to aromatic rings in a FriedelCrafts-type electrophilic substitution, which is directed and activated by the presence of phenolic groups.…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…The results of the pharmacological studies of hop extracts indicate the relationship between estrogenic activity of the objects and the fraction of prenyl flavonoids: xanthohumol (X), desmethylxanthohumol (DMX), isoxanthohumol (IX), 8-prenylnaringenin (8-PN) and 6-prenylnaringenin (6-PN). It has been found that the marked estrogenic activity of the polyphenolic fraction belongs to 8-PN and characterizes this compound as the most powerful pharmacological agent among the known phytoestrogens [7,8,10].…”
Section: Has Been Determined By Hplc In the Samples Of Liquid And Drymentioning
confidence: 99%
“…The results of the pharmacological studies of hop extracts indicate the relationship between estrogenic activity of the objects and the fraction of prenyl flavonoids: xanthohumol (X), desmethylxanthohumol (DMX), isoxanthohumol (IX), 8-prenylnaringenin (8-PN) and 6-prenylnaringenin (6-PN). It has been found that the marked estrogenic activity of the polyphenolic fraction belongs to 8-PN and characterizes this compound as the most powerful pharmacological agent among the known phytoestrogens [7,8,10].The process chain for obtaining APIs of the plant origin consists of different sets of operations performed according to the specific technological modes. Based on thermolabile properties of most substances of the plant origin the development of the technology for obtaining the corresponding APIs requires the study of dependence of the composition at each process stage involving heating of the product.…”
mentioning
confidence: 99%